Peritonitis, abscessation and haemorrhage: Complications of transcutaneous caecal decompression. (5th May 2014) - Unger, L.; Fouché, N.; Schnider, D.; Witte, S.
Summary Transcutaneous needle decompression of the caecum through the right flank is a valuable, routine procedure performed to resolve cases of large intestinal tympany. Nevertheless, it can be the cause of potentially life‐threatening complications as highlighted by the 3 cases presented in this case report. Abscess formation, septic peritonitis and haemorrhage following needle decompression are described.